Niat Menggunakan E-commerce: Suatu Pendekatan Technology Acceptance Models (Studi Pada Usaha Mikro, Kecil dan Menengah Di Kota Bengkulu) - Fatrisya Marsyadini; Nila Aprila (Jurnal Akuntansi, 2018)
This study was aimed to determine the effect of (1) the perceived ease of use, (2) the perceived usefulness, (3) the attitude towards using, and (4) the intention to use in using the E-commerce on the SMEs in Bengkulu city. The characteristics of the SMEs that were used in this study are the SMEs that are listed on the Department of Cooperatives and SMEs in Bengkulu city in the marketing field, that have not using the E-commerce for business activities yet, but already familiar with E-commerce in private, and already completed the training related to electronic commerce, SMEs recording and accounting. The populations in this study were the SMEs registered in the Department of Cooperatives and SMEs in Bengkulu City in the marketing field. Based on the Purposive Sampling Method, the samples obtained were 87 SMEs. The data is analyzed using SmartPLS 2.0 M3. The analysis shows that the perceived ease of use positively affects perceived usefulness, ease of use perceived positively effects the attitudes towards using, the perceived usefulness positively effects the attitudes towards using, the perceived usefulness positively effects the intention to use, and attitudes towards using positively influences the intention to use in using e-commerce in SMEs in Bengkulu city.Key words: perceived ease of use, perceived usefulness, attitude towards using, intention to use